2018
DOI: 10.1017/s0022149x18001153
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Raphidascaris (Nematoda: Raphidascarididae) infecting the fish Gymnogeophagus balzanii (Cichlidae) from the Pantanal wetlands, Brazil and a taxonomic update of the subgenera of Raphidascaris based on molecular phylogeny and morphology

Abstract: Raphidascaris (Sprentascaris) andersoni n. sp. (Nematoda: Raphidascarididae) collected in the intestine of the humphead cichlid Gymnogeophagus balzanii (Perugia) from the Pantanal wetlands, State of Mato Grosso do Sul (Brazil) is described and genetically characterized. The new species differs from its congeners mainly by having a conspicuous papilla-like formation slightly anterior to the cloacal aperture. Furthermore, males of R. (S.) lanfrediae and R. (S.) mahnerti have caudal alae, and R. (S.) hypostomi an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…The genus Raphidascaris was previously subdivided on morphological grounds into three subgenera – namely, Ichthyascaris Wu, 1949, Raphidascaris Railliet & Henry, 1915 and Sprentascaris Petter & Cassone, 1984 (Moravec et al ., 1990; Moravec & Nagasawa, 2002; Li et al ., 2012, 2016). Recent integrative taxonomic analyses have shown that Sprentascaris can be considered a separate valid genus (Malta et al ., 2018, 2020), a conclusion supported by our analyses (see fig. 3).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The genus Raphidascaris was previously subdivided on morphological grounds into three subgenera – namely, Ichthyascaris Wu, 1949, Raphidascaris Railliet & Henry, 1915 and Sprentascaris Petter & Cassone, 1984 (Moravec et al ., 1990; Moravec & Nagasawa, 2002; Li et al ., 2012, 2016). Recent integrative taxonomic analyses have shown that Sprentascaris can be considered a separate valid genus (Malta et al ., 2018, 2020), a conclusion supported by our analyses (see fig. 3).…”
Section: Discussionsupporting
confidence: 87%
“…The interrelationships of various ascaridoid taxa including the genus Raphidascaris are controversial, and the taxonomy and systematics of raphidascaridids are still in flux; the monophyly of Raphidascaris and Hysterothylacium remains doubtful (Malta et al ., 2018, 2020; this study). The genus Raphidascaris was previously subdivided on morphological grounds into three subgenera – namely, Ichthyascaris Wu, 1949, Raphidascaris Railliet & Henry, 1915 and Sprentascaris Petter & Cassone, 1984 (Moravec et al ., 1990; Moravec & Nagasawa, 2002; Li et al ., 2012, 2016).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations